2015
DOI: 10.1530/joe-15-0168
|View full text |Cite
|
Sign up to set email alerts
|

Histone deacetylase inhibition reduces hypothyroidism-induced neurodevelopmental defects in rats

Abstract: Thyroid hormone (TH) through its receptor (TRa/b) influences spatio-temporal regulation of its target gene repertoire during brain development. Though hypothyroidism in WT rodent models of perinatal hypothyroidism severely impairs neurodevelopment, its effect on TRa/b knockout mice is less severe. An explanation to this paradox is attributed to a possible repressive action of unliganded TRs during development. Since unliganded TRs suppress gene expression through the recruitment of histone deacetylase (HDACs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
(46 reference statements)
0
7
0
Order By: Relevance
“…A recent report shows that abnormal fetal brain development can be ameliorated by administering an HDAC inhibitor in the rat pups subjected to perinatal hypothyroidism. The HDAC inhibitor could restore TH-regulated genes such as BDNF , MBP , and PCP2 in the cerebellum and also reverse neurocognitive deficits in these rats [171]. In another study a case of pseudohypoparathyroidism in a baby girl was found to be associated with an altered methylation pattern of the GNAS gene, which encodes for an essential signal transduction molecule in various metabolic pathways [172].…”
Section: Maternal Metabolic Disordersmentioning
confidence: 99%
“…A recent report shows that abnormal fetal brain development can be ameliorated by administering an HDAC inhibitor in the rat pups subjected to perinatal hypothyroidism. The HDAC inhibitor could restore TH-regulated genes such as BDNF , MBP , and PCP2 in the cerebellum and also reverse neurocognitive deficits in these rats [171]. In another study a case of pseudohypoparathyroidism in a baby girl was found to be associated with an altered methylation pattern of the GNAS gene, which encodes for an essential signal transduction molecule in various metabolic pathways [172].…”
Section: Maternal Metabolic Disordersmentioning
confidence: 99%
“…Histone deacetylase inhibitors can inhibit deacetylation by HDAC. At present, the most well-studied HDAC inhibitors include sodium butyrate (SB) [18, 19], sodium valproate [20], and trichostatin [21], and SB is of great importance for ruminant animals [22, 23].…”
Section: Introductionmentioning
confidence: 99%
“…THs play an essential role in the growth and metabolic homeostasis in humans as well as in animals ( Prezioso et al, 2018 ). Triiodothyronine (T3), the active form of thyroid hormone, acts on its nuclear receptor and modulates target gene transcription ( Kumar et al, 2015 ). Even a 25% reduction in DDX3X levels strongly perturbs neurogenesis, suggesting the high dose-dependency of embryonic cortical development to DDX3X ( Lennox et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%